High-Fat Diet and Salivary Gland Alterations: A Scoping Review - Desiana Fitria; Putri Karisa; Fifi Veronica; Hanna Goenawan (Interdental Jurnal Kedokteran Gigi (IJKG), 2026)
Introduction: Obesity is a growing global health concern, largely driven by high-fat diet (HFD) consumption, which promotes adipose tissue accumulation and increases metabolic disorder risk. Beyond systemic effects, obesity may impair salivary gland function, which is essential for maintaining oral homeostasis. However, evidence regarding the effects of HFDs on salivary glands remains fragmented and inconsistent. This scoping review aimed to map the literature on HFD-induced salivary gland alterations and elucidate the underlying biological mechanisms. Review: The review followed PRISMA-ScR guidelines. Relevant studies were identified through comprehensive searches of PubMed and Scopus and screened using predefined eligibility criteria. Twenty-two studies were included. HFDs affected four major aspects of salivary gland physiology: reduced antioxidant and digestive enzyme activity; altered salivary proteins, including mucin and IgA; increased inflammatory biomarkers and oxidative stress; and morphological and functional changes, including reduced salivary secretion, fibrosis, vacuolization, inflammatory infiltration, and lipid accumulation. However, some studies reported no significant changes, suggesting that responses may vary according to gland type, HFD exposure duration, and metabolic status. Conclusion: HFD consumption induces oxidative stress, inflammation, and structural and molecular alterations in salivary glands, potentially contributing to salivary dysfunction. Further longitudinal and translational studies are needed to clarify the underlying mechanisms and clinical implications.